1999
DOI: 10.1136/bmj.318.7198.1591
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for erysipelas of the leg (cellulitis): case-control study

Abstract: Objective To assess risk factors for erysipelas of the leg (cellulitis). Design Case-control study. Setting 7 hospital centres in France. Subjects 167 patients admitted to hospital for erysipelas of the leg and 294 controls. Results In multivariate analysis, a disruption of the cutaneous barrier (leg ulcer, wound, fissurated toe-web intertrigo, pressure ulcer, or leg dermatosis) (odds ratio 23.8, 95% confidence interval 10.7 to 52.5), lymphoedema (71.2, 5.6 to 908), venous insufficiency (2.9, 1.0 to 8.7), leg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
319
8
19

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(360 citation statements)
references
References 18 publications
14
319
8
19
Order By: Relevance
“…[14][15][16][17] These studies showed that disruption of the cutaneous barrier (leg ulcer, wound, fissurated toe-web intertrigo, pressure ulcer, or leg dermatosis), venous insufficiency, leg edema, being overweight, fungal infections, history of cellulitis, chronic venous insufficiency, prior saphenectomy, white race, and the presence of Staphylococcus aureus and/or B-hemolytic streptococci in the toe webs to be independently associated with cellulitis.…”
mentioning
confidence: 99%
“…[14][15][16][17] These studies showed that disruption of the cutaneous barrier (leg ulcer, wound, fissurated toe-web intertrigo, pressure ulcer, or leg dermatosis), venous insufficiency, leg edema, being overweight, fungal infections, history of cellulitis, chronic venous insufficiency, prior saphenectomy, white race, and the presence of Staphylococcus aureus and/or B-hemolytic streptococci in the toe webs to be independently associated with cellulitis.…”
mentioning
confidence: 99%
“…Estudios recientes han permitido precisar condiciones locales y sistémicas que predisponen al desarrollo de erisipela 6 . La importancia de reconocer estos factores es determinante para evitar un primer episodio o la recurrencia de esta enfermedad.…”
Section: Factores De Riesgo Para Erisipela Y Celulitisunclassified
“…Otros factores corresponden a la presencia de insuficiencia venosa, edema de la extremidad, sobrepeso u obesidad. Estos estudios no han logrado demostrar que la diabetes mellitus sea un factor de riesgo independiente 6 . El factor más frecuente en la población es la presencia de intertrigo fisurado.…”
Section: Factores De Riesgo Para Erisipela Y Celulitisunclassified
“…It is an infectious lymphangitis marked by a red skin-rash with a sharply demarcated raised edge, spread along the lymph capillary network and also affecting the lymph nodes. 2 This occurs not only in non-infectious lymphangitis, but also in the recurrent episodes of erysipelas suffered by elderly or immunodepressed patients, due to lymphatic impairment. The exudate of protein, fibrin and figurata elements, as well as endothelial damage causing thrombosis of the lymphatic trunk, eventually leads to edema and lymphedema.…”
Section: ©2011 By Anais Brasileiros De Dermatologiamentioning
confidence: 99%